IMPLEMENTASI METODE TUTOR SEBAYA DALAM MENINGKATKAN KEMAMPUAN MEMBACA AL-QUR’AN SISWA (Studi Kualitatif Naturalistik Di SMA Martia Bhakti Kayu Ringin Bekasi Selatan Kota Bekasi) - Sri Yunita; Siti Asiah (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam UNISMA Bekasi, 2022)
Peer tutoring is a learning method that is carried out by selecting students who have more abilities than others to guide other students who have abilities below them. The research in this thesis formulates three main problems, namely:How is the implementation of the peer tutoring method at Martia Bhakti High School Bekasi and What are the supporting factors and inhibiting factors in the application of the peer tutor method at Martia Bhakti High School Bekasi. The purpose of the study was to determine the implementation of the peer tutoring method as well as the supporting and inhibiting factors for the application of the peer tutor method in improving students' reading skills of the Koran at SMA Martia Bhakti Bekasi.The research in this thesis uses naturalistic qualitative research, namely research that is based on a phenomenological view and seeks to understand the meaning of events and their relation to the object of research. The results showed that the peer tutoring method at SMA Martia Bhakti Bekasi did not cover the maturity of planning, implementation of organizing activities and evaluating activities. This can be confirmed because the peer tutoring method at SMA Martia Bhakti Bekasi has not become the main program in learning the Qur'an. The factors that support the application of peer tutors at SMA Martia Bhakti Bekasi include the enthusiasm of students in reciting the Qur'an, the cohesiveness of teachers in teaching the Qur'an, and encouragement from parents or guardians of students. While the inhibiting factors, time constraints, quality of tutors (tutor standardization), there are no specific guidelines for learning the Koran using peer tutors and have not made peer tutors the main program in learning the Koran.